Roles of Capsule Endoscopy and Single-Balloon Enteroscopy in Diagnosing Unexplained Gastrointestinal Bleeding - Shohei Ooka; Kiyonori Kobayashi; Kana Kawagishi; Masaru Kodo; Kaoru Yokoyama; Miwa Sada; Satoshi Tanabe; Wasaburo Koizumi (Clinical Endoscopy, 2016)
Background/Aims: The diagnostic algorithms used for selecting patients with obscure gastrointestinal bleeding (OGIB) for capsule endoscopy (CE) or balloon-assisted enteroscopy (BE) vary among facilities. We aimed to demonstrate the appropriate selection criteria of CE and single balloon-assisted enteroscopy (SBE) for patients with OGIB according to their conditions, by retrospectively comparing the diagnostic performances of CE and BE for detecting the source of the OGIB. Methods: We investigated 194 patients who underwent CE and/or BE. The rate of positive findings, details of the findings, accidental symptoms, and hemostasis methods were examined and analyzed. Results: CE and SBE were performed in 103 and 91 patients, respectively, and 26 patients underwent both examinations. The rate of positive findings was significantly higher with SBE (73.6%) than with CE (47.5%, p<0.01). The rate of positive findings was higher in overt bleeding cases than in occult bleeding cases for both BE and SBE. Among the overt bleeding cases, the rate was significantly higher in ongoing bleeding cases than in previous bleeding cases. Conclusions: Both CE and SBE are useful to diagnose OGIB. For overt bleeding cases and ongoing bleeding cases, SBE may be more appropriate than CE because endoscopic diagnosis and treatment can be completed simultaneously.